Scientific Ethics and Academic Integrity: Literature Review (Научни трудове на УНСС, 2024)
Scientific ethics and academic integrity are foundational principles in the pursuit of knowledge and the advancement of society. This literature review examines the importance of ethical conduct in scientific research and the implications of academic dishonesty on the integrity of the academic community. Ethical considerations in scientific research encompass a wide range of issues, including plagiarism, data fabrication, and conflicts of interest. Violations of scientific ethics not only undermine the credibility of research findings but also erode public trust in the scientific community. Upholding academic integrity ensures the credibility of academic credentials and promotes a culture of honesty and trust in the academic community.